Applying scientific principles to enhance paralympic classification now and in the future: A research primer for rehabilitation specialists - Tweedy, S. M.; Connick, M. J.; Beckman, E. M. (Physical Medicine & Rehabilitation Clinics of North America, 2018)
Para-sport classification systems define eligibility for Para sport and provide a competition structure that controls for the impact of impairment on the outcome of competition. This article focuses on the classification of para athletes with physical impairments. Development of classification systems based on scientific evidence has only recently been made possible by adoption of a statement of the purpose of classification by the International Paralympic Committee and its member organizations. Rigorous descriptive science can improve extant systems of classification and a recently published study described a data-driven classification structure with validity superior to that of the extant system.